2005
DOI: 10.1542/peds.2005-0885
|View full text |Cite
|
Sign up to set email alerts
|

How Do Physicians Immunize Their Own Children? Differences Among Pediatricians and Nonpediatricians

Abstract: ABSTRACT. Context. Immunization has an essential impact on public health worldwide. Numerous studies have shown the efficacy of different vaccines to protect individuals from various diseases. However, some parents choose not to vaccinate their children for reasons such as, among others, doubts regarding their usefulness, concerns over safety or efficacy, etc. Physicians are known to exert a direct influence on immunization rates by answering questions and clarifying misconceptions. Yet, it is unknown how they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 32 publications
4
44
0
3
Order By: Relevance
“…Health professionals' knowledge and attitudes about vaccines have previously been shown to be an important determinant of their own vaccine uptake, their intention to recommend the vaccine to their patients and the vaccine uptake of their patients. 8,[21][22][23][24][25] To conclude, results of this study indicate an overall high acceptability of seasonal influenza vaccination among Quebec vaccine providers. Despite the fact that vaccine providers held positive attitudes toward LAIV, the low uptake for LAIV observed in Quebec despite free vaccines and preferential recommendation to use LAIV over TIV warrants further studies.…”
Section: Discussionmentioning
confidence: 55%
“…Health professionals' knowledge and attitudes about vaccines have previously been shown to be an important determinant of their own vaccine uptake, their intention to recommend the vaccine to their patients and the vaccine uptake of their patients. 8,[21][22][23][24][25] To conclude, results of this study indicate an overall high acceptability of seasonal influenza vaccination among Quebec vaccine providers. Despite the fact that vaccine providers held positive attitudes toward LAIV, the low uptake for LAIV observed in Quebec despite free vaccines and preferential recommendation to use LAIV over TIV warrants further studies.…”
Section: Discussionmentioning
confidence: 55%
“…71 However, more research is needed to assess whether individuals who already professionals' knowledge and attitudes about vaccines have previously been shown to be an important determinant of their own vaccine uptake, their intention to recommend the vaccine to their patients and the vaccine uptake of their patients. [92][93][94][95][96][97] Findings of a review on determinants of nurses' practices regarding influenza vaccination indicate a relationship between knowledge, attitudes and vaccination practices. In the 12 research studies included in this review, higher knowledge and positive attitudes toward influenza vaccination were positively associated with vaccination coverage among nurses and there was also an association between nurses' vaccination status and their reported promotion of vaccination to their patients.…”
Section: The Role Of Public Health and Vaccine Policiesmentioning
confidence: 99%
“…The authors concluded that fear of "immune overload" among these health care providers means that they are unlikely to answer parental concerns adequately. 94 Health professionals are generally strong supporters of vaccination. However, some of them could be categorized as vaccinehesitant.…”
Section: The Role Of Public Health and Vaccine Policiesmentioning
confidence: 99%
“…Little is documented, however, on how pediatricians vaccinate their children overall [6]. One study in 2005 examined how 93% of Swiss physicians followed immunization recommendations in that country, but no duplicate study has been performed in the United States to date [7]. A number of prior studies have examined reported acceptance of new vaccines including rotavirus, but not their acceptance of the overall vaccine schedule of the Advisory Committee on Immunization Practices (ACIP) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%